Method for preparing hydrophobic nanocellulose aerogel by taking vinasse residues as raw materials
By preparing the lees slag into a hydrophobic nanocellulose aerogel, the problems of insufficient hydrophilicity and mechanical stability of traditional nanocellulose aerogels are solved, efficient oil-water separation and reusability are achieved, and the lees slag is promoted. Resource utilization.
Patent Information
- Application Number
- CN202411525386.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-27
AI Technical Summary
The hydrophilicity and mechanical stability of traditional nanocellulose aerogels are insufficient, which affects its oil-water separation efficiency and reusable performance.
Use wine lees as raw material to prepare hydrophobic nanocellulose aerogels through washing, drying, grinding, reaction of alkali and bleach, TEMPO oxidation, dialysis, freeze-drying, polyvinyl alcohol mixing, chemical vapor deposition and other steps to improve the Its size distribution, aspect ratio, porosity and hydrophobic properties.
The prepared hydrophobic nanocellulose aerogel has ultra-low density, ultra-high porosity and excellent hydrophobic properties, which significantly improves oil-water separation efficiency and durability, and realizes the resource processing and high-value utilization of wine lee slags.
Smart Images

Figure CN119192664A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a method for preparing hydrophobic nano cellulose aerogel by taking wine lees as raw material. Background Art
[0002] Wine lees have high water content and high acidity, and are very easy to rot and deteriorate. Improper treatment will pollute the soil and affect the environment, and it is considered light industrial waste. At the same time, wine lees are also considered biomass energy because they are rich in nutrients such as cellulose and protein, and have high utilization value and huge resource potential. It is imperative to achieve the reduction, harmlessness and resource utilization of wine lees.
[0003] Nanocellulose is a fiber with a diameter of less than 100nm extracted from natural cellulose. It is an emerging nanomaterial. It is derived from cellulose that is widely present in nature. After being processed by specific technical means, it becomes a nanoscale material. Nanocellulose not only inherits the excellent properties of cellulose itself, such as biodegradability and biocompatibility, but also exhibits unique physical, chemical and mechanical properties, such as high Young's modulus, high specific surface area, strong hydrophilicity, etc. It has broad application prospects in the fields of food, medicine, energy, water treatment and composite materials, and has received widespread attention from scientific researchers and industry worldwide in recent years.
[0004] With the acceleration of industrialization and the growing demand for energy, the use of fossil fuels such as petroleum has increased dramatically, resulting in increasingly serious oil pollution problems in water bodies. The development of efficient and environmentally friendly oil-water separation technology has become one of the current research hotspots in the field of environmental protection. As a new type of three-dimensional porous material, nanocellulose aerogel has light weight, high porosity, large specific surface area and excellent adsorption performance, showing great potential in the field of oil-water separation. Its unique three-dimensional network structure provides an effective separation channel for oil-water mixtures. At the same time, the hydrophilicity and biodegradability of nanocellulose also provide guarantees for the environmental protection of the material. The hydrophilicity, insufficient oil absorption capacity and poor mechanical stability of traditional nanocellulose aerogels affect their reusability. Therefore, it is necessary to functionally modify nanocellulose aerogels in order to improve their oil-water separation efficiency and durability. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing nanocellulose aerogel using light industrial waste as raw material. The nanocellulose prepared by this method has a larger size distribution and a higher aspect ratio. The obtained aerogel has ultra-low density and ultra-high porosity, and exhibits excellent hydrophobic properties after modification.
[0006] The technical solution provided by the present invention is as follows: A method for preparing hydrophobic nanocellulose aerogel using vinasse as raw material comprises the following steps: washing and drying the vinasse, grinding it and mixing it with a pretreatment liquid to remove impurities to obtain vinasse powder; reacting the vinasse powder with an alkali solution and a bleaching liquid respectively to obtain cellulose; subjecting the cellulose to TEMPO oxidation and ultrasound, dialysis treatment and freeze drying to obtain nanocellulose; mixing the nanocellulose with a polyvinyl alcohol solution, freeze drying to obtain a nanocellulose aerogel, and then performing silanization modification by chemical vapor deposition to obtain a hydrophobic nanocellulose aerogel.
[0007] Furthermore, the lees are completely soaked with water at about 70-90°C before washing, and then washed with deionized water until the filtrate is clear, and then placed in an oven at 60-80°C for drying.
[0008] Furthermore, the pretreatment liquid is a mixture of toluene and ethanol, the volume ratio of toluene to ethanol is 1-3:1, and the ratio of vinasse to pretreatment liquid is 1:12-15.
[0009] Furthermore, the wine lees are immersed in a pretreatment liquid with dynamic heating and stirring at a temperature of 90-110°C for 6-8 hours; after being treated with the pretreatment liquid, they are washed with ethanol and deionized water in sequence, and then placed in a 60°C-80°C oven for drying and preservation.
[0010] Furthermore, the alkali solution is a 5%-15% KOH solution; the reaction temperature of the vinasse powder and the alkali solution is 70-90°C, the reaction time is 2-4h, and the solid-liquid ratio is 1:15-35; the bleaching solution is a 1.5%-7.5% NaClO2 solution; the reaction temperature of the vinasse powder and the bleaching solution is 75-95°C, the reaction time is 1.5-2.5h, and the solid-liquid ratio is 1:30-35; acetic acid is used to adjust the pH during the reaction of the vinasse powder and the bleaching solution so that the pH is maintained at 3-4; the filter residue after the alkali solution treatment and the bleaching solution treatment is repeatedly washed with deionized water until the filtrate is neutral, and then placed in a 60-80°C oven for drying.
[0011] Furthermore, the TEMPO oxidation adopts a TEMPO / NaBr / NaClO catalytic oxidation system, the mass ratio of TEMPO to NaBr is 1:5-16, the mass ratio of cellulose to NaBr is 1:0.16-0.33, and the amount of NaClO is 5-30mmol / g cellulose; before the TEMPO oxidation reaction, the cellulose is dispersed in ultrapure water with a solid-liquid ratio of 1:80-120, and stirred at room temperature for 1-2h; the TEMPO oxidation reaction is carried out in an ultrasonic cleaner throughout the process, the ultrasonic power is 30-50kHz, and the temperature is controlled at 25 (±5)°C by a cooling circulating fluid.
[0012] Furthermore, during the TEMPO oxidation reaction, HCl and NaOH were used to maintain the pH of the reaction in the range of 10 to 11; when the pH remained constant, 5 to 30 ml of anhydrous ethanol was poured in to quench the oxidation reaction; a dialysis bag with a molecular weight of 8000 to 14000 was used for dialysis, and the dialysis time was 3 to 5 days. After dialysis, a nanocellulose suspension was obtained, and nanocellulose was obtained after freeze-drying.
[0013] Furthermore, the modifier used for silanization modification is methyltrimethoxysilane, the modification temperature is 70-80°C, and the time is 5-7h.
[0014] Furthermore, the method comprises: (1) Pretreatment: The vinasse is washed with water and dried, ground and mixed with a pretreatment liquid to remove impurities such as protein, lipid pectin, and obtain vinasse powder.
[0015] (2) Preparation of nanocellulose: First, the lees powder is reacted with alkali solution and bleaching solution to obtain cellulose. Then, TEMPO oxidation is used to prepare nanocellulose. The TEMPO oxidation is performed with ultrasound. The liquid obtained after oxidation is transferred to a dialysis bag and dialyzed for 3-5 days. Nanocellulose is obtained after freeze-drying.
[0016] (3) Aerogel preparation and modification: Nanocellulose is mixed with polyvinyl alcohol solution and freeze-dried to obtain aerogel. Then, it is silanized by chemical vapor deposition to obtain modified aerogel. The modified aerogel exhibits excellent hydrophobic properties and can adsorb a large amount of oil substances, which has great development potential in the field of oil-water separation.
[0017] Preferably, in step (1), the vinasse residue is completely soaked in warm water at about 80°C before washing, and then washed with deionized water until the filtrate is clear, and then placed in an oven at 60°C-80°C for drying, and the moisture content of the vinasse residue is maintained at 10%-20% by drying.
[0018] Preferably, in step (1), the dried vinasse is ground, and the sample retained on the 60-mesh sieve is collected to remove powder that is too small or too large.
[0019] Preferably, in step (1), the pretreatment liquid is a mixture of toluene and ethanol (the volume ratio of toluene to ethanol is 2:1), which is mixed with the pretreatment liquid at a solid-liquid ratio of 1:12-1:15.
[0020] Preferably, in step (1), the vinasse is immersed in the pretreatment liquid with dynamic heating and stirring at a temperature of 110° C. for 6-8 hours.
[0021] More preferably, in step (2), the reaction temperature of the vinasse and the bleaching liquid is 75° C.-95° C., the reaction time is 2 h, and the solid-liquid ratio is 1:30-1:35.
[0022] Preferably, in step (2), the TEMPO oxidation reaction needs to be carried out in an ultrasonic cleaner throughout the entire process, with the ultrasonic power at 40 kHz and the temperature controlled at 25 (±5) °C by a cooling circulating fluid.
[0023] Preferably, in step (3), the mass fraction of nanocellulose in the aqueous solution is 0.5%, and the mass fraction of polyethanol in the aqueous solution is 0.3%-1.0%. First, polyvinyl alcohol is fully dissolved in water, and then mixed with nanocellulose, and then freeze-dried to obtain aerogel. By chemical vapor deposition, silane is coated on the aerogel network to form a hydrophobic layer, and a hydrophobic nanocellulose aerogel can be obtained.
[0024] Preferably, in step (3), the modifier is methyltrimethoxysilane (MTMS), the modification temperature is 70°C-80°C, and the modification time is 6 hours to obtain modified nanocellulose aerogel.
[0025] The present invention also provides a hydrophobic nano-cellulose aerogel, which is prepared by the above method.
[0026] The present invention also provides application of the hydrophobic nanocellulose aerogel in oil pollution adsorption. Beneficial Effects
[0027] When the method of the present invention utilizes wine lees to prepare nanocellulose, the TEMPO oxidation process is carried out in an ultrasonic cleaner, and the reaction temperature is controlled by cooling the circulating fluid. The full participation of ultrasound in the reaction process can firstly effectively break up the cellulose raw material, avoid aggregation, and obtain a highly uniformly dispersed nanocellulose suspension; secondly, it can fully contact and react with the oxidant to improve the reaction efficiency, and the obtained nanocellulose has a higher aspect ratio; at the same time, ultrasound makes the size and morphology of the obtained nanocellulose more uniform, which is conducive to the application of nanocellulose aerogel in the adsorption field.
[0028] The present invention uses distiller's grains residue from light industrial waste as a raw material for the preparation and functional application of nanocellulose aerogel, the method is simple and efficient, the obtained nanocellulose has a large size distribution and a high aspect ratio, the prepared aerogel has ultra-low density and ultra-high porosity, and exhibits excellent hydrophobic properties after modification. On the one hand, the resource processing of distiller's grains residue can be realized, and on the other hand, the added value and utilization rate of distiller's grains residue are improved, which is conducive to the development of high-value utilization technology of distiller's grains residue. It broadens the high-value application path of distiller's grains residue from waste to treasure, and provides ideas for the field of water treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Flowchart for the preparation and modification of nanocellulose aerogels from wine lees. DETAILED DESCRIPTION
[0030] Through specific implementation cases, the specific method for preparing nanocellulose aerogel using wine lees as raw material and the modification thereof proposed by the present invention, as well as the effects thereof are described in detail as follows.
[0031] Reference Figure 1 , a method for preparing nanocellulose using wine lees as raw material, comprising the following steps: (1) Pretreatment: The wine lees are washed with water and dried, ground and mixed with the pretreatment liquid to remove impurities such as protein, lipids, and pectin.
[0032] (2) Preparation of nanocellulose: First, the treated powder is reacted with alkali solution and bleaching solution to obtain cellulose. Then, TEMPO oxidation is used to prepare nanocellulose. The TEMPO oxidation is performed with ultrasound. The suspension obtained after oxidation is dialyzed for 3-5 days and then freeze-dried to obtain nanocellulose.
[0033] (3) Preparation and modification of aerogel: The obtained nanocellulose is mixed with polyvinyl alcohol and freeze-dried to obtain aerogel. Then, it is silanized by chemical vapor deposition to obtain modified aerogel. The modified aerogel exhibits excellent hydrophobic properties, can adsorb a large amount of oil substances, and is reusable, which has great development potential in the field of oil-water separation. Example 1
[0034] A method for preparing hydrophobic nanocellulose aerogel using sorghum wine lees as raw material, comprising the following steps: (1) Pretreatment: Soak the sorghum lees in warm water at 70°C overnight, then filter and wash with clean water until the filtrate is clear; then place in a 60°C forced air drying oven to dry so that the moisture content is maintained at 10%; finally grind with a crusher, sieve, and collect the lees powder on the 60-mesh sieve. Take 5g of lees powder, mix with 20mL of anhydrous ethanol and 40mL of toluene, and stir and heat at 110°C for 6h. After the reaction is completed, wash the filter residue with anhydrous ethanol and ultrapure water in turn, and then place in a 60°C forced air drying oven to dry.
[0035] (2) Cellulose extraction: Take 3 g of the sample obtained in step (1), mix it with 95 g of 10% KOH solution, and stir and heat it at 90°C for 4 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Then take 2 g of the dried filter residue and mix it with 66 g of 7.5% NaClO2 solution, adjust the pH to 3-4 with acetic acid, and stir and heat it at 75°C for 2 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Collect the filter residue and dry it in a 60°C forced air drying oven to obtain cellulose.
[0036] (3) Preparation of nanocellulose: Take 1g of cellulose obtained in step (2), disperse it in 100mL of deionized water, and stir it on a magnetic stirrer for 1h. Then add 0.33g of NaBr and 0.033g of TEMPO, move it into an ultrasonic cleaner and continue stirring. After adding 20mmol of NaClO, the oxidation reaction begins. As the reaction proceeds, the pH of the system will change. NaOH and HCl need to be used to maintain the reaction pH at 10.2. When the reaction pH remains constant, pour 15mL of anhydrous ethanol to quench the oxidation reaction and the reaction ends. The frequency of the ultrasonic cleaner is 40khz. Long-term ultrasound will increase the temperature. The temperature of the circulating liquid needs to be controlled at 25 (±5)℃. After the reaction is completed, all the liquid is transferred to a dialysis bag with a molecular weight of 8000-14000 and dialyzed for 4d. After the dialysis is completed, a nanocellulose suspension is obtained, and U-nanocellulose is obtained by freeze drying. At the same time, nanocellulose that is not in the ultrasonic cleaner is prepared under the same conditions to obtain N-nanocellulose.
[0037] (4) Preparation and modification of aerogel: Take 0.3g of polyvinyl alcohol and thoroughly dissolve it in 99.2g of deionized water, then add 0.5g of U-nanocellulose and N-nanocellulose respectively. Place the two mixed solutions in an ultrasonic container for 30 minutes to fully cross-link the nanocellulose and polyvinyl alcohol. Then freeze-dry the two mixed solutions to obtain U-nanocellulose aerogel and N-nanocellulose aerogel respectively. Place the aerogel together with 1mL of deionized water and 3mL of MTMS in a sealed container and carry out chemical vapor deposition reaction in a vacuum drying oven at 70°C. After 6 hours, U-nanocellulose modified aerogel and N-nanocellulose modified aerogel were obtained respectively.
[0038] (5) To verify the hydrophobic effect of aerogels, two aerogels of the same mass were immersed in an oil-water mixture (the mass of the mixture was equal, the mass ratio of the oil and dirt was the same, and the oil and dirt could be dyed with Sudan red dye). It can be observed that the U-nanocellulose modified aerogel floated on the water surface and quickly adsorbed the oil and dirt and still floated on the water surface. The N-nanocellulose aerogel failed to absorb all the oil and dirt and was partially immersed in the water.
[0039] Through this experiment, it was found that the density of U-nanocellulose modified aerogel was 2.31kg / m 3 The porosity is 99.88%, the water contact angle is 146.6°, and the adsorption amount of oil is about 89g / g; the density of N-nanocellulose modified aerogel is 6.96 kg / m 3 , porosity is 99.62%, water contact angle is 118.5°, and oil adsorption capacity is 46g / g. The performance of U-nanocellulose modified aerogel is better than that of N-nanocellulose modified aerogel. This is because, during the preparation of nanocellulose, the ultrasound provided by the ultrasonic cleaner makes the cellulose more evenly dispersed during the oxidation process, and the obtained nanocellulose reduces the phenomenon of pore reduction caused by fiber bundle aggregation. In the hydrophobic modification, silane fully reacts with the uniformly distributed hydroxyl groups on the nanocellulose aerogel, thereby obtaining a nanocellulose modified aerogel with excellent hydrophobic effect. Example 2
[0040] This example provides a method for preparing hydrophobic nanocellulose aerogel using sorghum wine lees as raw material, the steps are: (1) Pretreatment: Soak the sorghum lees in warm water at 70°C overnight, then filter and wash with clean water until the filtrate is clear; then place in a 60°C forced air drying oven to dry so that the moisture content is maintained at 10%; finally grind with a crusher, sieve, and collect the lees powder on the 60-mesh sieve. Take 5g of lees powder, mix with 22.5mL of anhydrous ethanol and 45mL of toluene, and stir and heat at 110°C for 6h. After the reaction is completed, wash the filter residue with anhydrous ethanol and ultrapure water in turn, and then place in a 60°C forced air drying oven to dry.
[0041] (2) Cellulose extraction: Take 3 g of the sample obtained in step (1), mix it with 75 g of 5% KOH solution, and stir and heat it at 80°C for 3 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Then take 2 g of the dried filter residue and mix it with 60 g of 3% NaClO2 solution, adjust the pH to 3-4 with acetic acid, and stir and heat it at 80°C for 2 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Collect the filter residue and dry it in a 60°C forced air drying oven to obtain cellulose-Ⅰ. Under the same conditions, mix the alkali-treated filter residue with 40 g of 3% NaClO2 solution for cellulose extraction experiment to obtain cellulose-Ⅱ.
[0042] (3) Preparation of nanocellulose: Take 1g of cellulose obtained in step (2), disperse it in 100mL of deionized water, and stir it on a magnetic stirrer for 1h. Then add 0.16g of NaBr and 0.016g of TEMPO, move it into an ultrasonic cleaner and continue stirring. After adding 15mmol of NaClO, the oxidation reaction begins. As the reaction proceeds, the pH of the system will change. NaOH and HCl need to be used to maintain the reaction pH at 10.5. When the reaction pH remains constant, pour 15mL of anhydrous ethanol to quench the oxidation reaction and the reaction ends. The frequency of the ultrasonic cleaner is 40khz. Long-term ultrasound will increase the temperature. The temperature of the cooling circulating fluid needs to be controlled at 25 (±5)℃. After the reaction is completed, all the liquid is transferred to a dialysis bag with a molecular weight of 8000-14000 and dialyzed for 4d. After the dialysis is completed, a nanocellulose suspension is obtained, and nanocellulose-Ⅰ and nanocellulose-Ⅱ are obtained by freeze drying.
[0043] (4) Preparation and modification of aerogel: Take 0.6g of polyvinyl alcohol and thoroughly dissolve it in 98.9g of deionized water, then add 0.5g of nanocellulose. Place the mixed solution in an ultrasonic container for 30 minutes to fully cross-link the nanocellulose and polyvinyl alcohol. Then freeze-dry the mixed solution to obtain nanocellulose aerogel. The aerogel is placed in a sealed container with 1mL of deionized water and 3mL of MTMS, and a chemical vapor deposition reaction is carried out in a vacuum drying oven at 70°C. After 6 hours, modified aerogels are obtained. They are nanocellulose modified aerogel-Ⅰ and nanocellulose modified aerogel-Ⅱ respectively.
[0044] Through this experiment, it was found that the density of nanocellulose modified aerogel-Ⅰ is 3.89kg / m 3 The porosity is 99.72%, the water contact angle is 142.9°, and the oil adsorption capacity is about 70g / g. The density of nanocellulose modified aerogel-Ⅱ is 4.53kg / m 3 , the porosity is 99.66%, the water contact angle is 140.2°, and the amount of oil adsorbed is about 58g / g. The performance of the two aerogels is similar. The slight difference is due to the different ratios of solids to bleaching liquid. Insufficient bleaching liquid affects the extraction effect and purity of cellulose. During the extraction of cellulose, the bleaching liquid can remove the remaining lignin, while improving the color of cellulose and increasing the whiteness. During the extraction of cellulose II, the ratio of solids to bleaching liquid is 1:20. Insufficient bleaching liquid leads to insufficient removal of impurities such as lignin. In the subsequent preparation and modification of nanocellulose, the lower cellulose purity affects the performance of the aerogel. Example 3
[0045] A method for preparing hydrophobic nanocellulose aerogel using sorghum wine lees as raw material, comprising the following steps: (1) Pretreatment: Soak the sorghum lees in warm water at 70°C overnight, then filter and wash with clean water until the filtrate is clear; then place in a 60°C forced air drying oven to dry so that the moisture content is maintained at 10%; finally grind with a crusher, sieve, and collect the lees powder on the 60-mesh sieve. Take 5g of lees powder, mix with 20mL of anhydrous ethanol and 40mL of toluene, and stir and heat at 110°C for 6h. After the reaction is completed, wash the filter residue with anhydrous ethanol and ultrapure water in turn, and then place in a 60°C forced air drying oven to dry.
[0046] (2) Cellulose extraction: Take 3 g of the sample obtained in step (1), mix it with 95 g of 10% KOH solution, and stir and heat it at 90°C for 4 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Then take 2 g of the dried filter residue and mix it with 66 g of 7.5% NaClO2 solution, adjust the pH to 3-4 with acetic acid, and stir and heat it at 75°C for 2 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Collect the filter residue and dry it in a 60°C forced air drying oven to obtain cellulose.
[0047] (3) Preparation of nanocellulose: Take 1g of cellulose obtained in step (2), disperse it in 100mL of deionized water, and stir it on a magnetic stirrer for 1h. Then add 0.33g of NaBr and 0.033g of TEMPO, move it into an ultrasonic cleaner and continue stirring. After adding 20mmol of NaClO, the oxidation reaction begins. As the reaction proceeds, the pH of the system will change. NaOH and HCl need to be used to maintain the reaction pH at 10.2. When the reaction pH remains constant, pour 15mL of anhydrous ethanol to quench the oxidation reaction and the reaction ends. The frequency of the ultrasonic cleaner is 40khz. Long-term ultrasound will increase the temperature. The temperature of the cooling circulating fluid needs to be controlled at 25 (±5)℃. After the reaction is completed, all the liquid is transferred to a dialysis bag with a molecular weight of 8000-14000 and dialyzed for 4d. After the dialysis is completed, a nanocellulose suspension is obtained, and nanocellulose is obtained by freeze drying.
[0048] (4) Preparation and modification of aerogel: Take 0.3g of polyvinyl alcohol and thoroughly dissolve it in 99.2g of deionized water, then add 0.5g of nanocellulose. Place the mixture in an ultrasonic container for 30 minutes to fully cross-link the nanocellulose and polyvinyl alcohol. Then freeze-dry the mixture to obtain nanocellulose aerogel. Place the aerogel together with 1mL of deionized water and 3mL of MTMS in a sealed container and perform chemical vapor deposition in a 70°C forced air drying oven. After 6 hours, nanocellulose modified aerogel is obtained.
[0049] (5) To verify the hydrophobic effect of aerogels, the aerogels were immersed in an oil-water mixture (the oil stains can be dyed with Sudan red dye). It can be observed that the nanocellulose aerogels sank to the bottom of the liquid and only adsorbed a small amount of oil stains.
[0050] Through this experiment, it was found that chemical vapor deposition in a forced air drying oven did not produce hydrophobicity. This is because chemical vapor deposition modification is to form a hydrophobic coating on the aerogel network by coating the synthesized silane gas. The silane gas synthesized in the forced air drying oven will be sucked out of the cavity, and insufficient silane gas participating in the reaction will lead to insufficient modification. Example 4
[0051] A method for preparing hydrophobic nanocellulose aerogel using wheat straw as raw material, comprising the following steps: (1) Pretreatment: Soak the wheat straw in warm water at 70°C overnight, then filter and wash with clean water until the filtrate is clear; then place it in a 60°C forced air drying oven to dry it so that the moisture content is maintained at 10%; finally grind it with a crusher, sieve it, and collect the lees powder on the 60-mesh sieve. Take 5g of wheat straw powder, mix it with 20mL of anhydrous ethanol and 40mL of toluene, and stir and heat it at 110°C for 6h. After the reaction is completed, wash the filter residue with anhydrous ethanol and ultrapure water in turn, and then place it in a 60°C forced air drying oven to dry it.
[0052] (2) Cellulose extraction: Take 3 g of the sample obtained in step (1), mix it with 90 g of 10% KOH solution, and stir and heat it at 80°C for 3 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Then take 2 g of the dried filter residue and mix it with 70 g of 7.5% NaClO2 solution, adjust the pH to 3-4 with acetic acid, and stir and heat it at 75°C for 2 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Collect the filter residue and dry it in a 60°C forced air drying oven to obtain cellulose.
[0053] (3) Preparation of nanocellulose: Take 1g of cellulose obtained in step (2), disperse it in 100mL of deionized water, and stir it on a magnetic stirrer for 1h. Then add 0.33g of NaBr and 0.033g of TEMPO, move it into an ultrasonic cleaner and continue stirring. After adding 20mmol of NaClO, the oxidation reaction begins. As the reaction proceeds, the pH of the system will change. NaOH and HCl need to be used to maintain the reaction pH at 10.2. When the reaction pH remains constant, pour 15mL of anhydrous ethanol to quench the oxidation reaction and the reaction ends. The frequency of the ultrasonic cleaner is 40khz. Long-term ultrasound will increase the temperature. The temperature of the cooling circulating fluid needs to be controlled at 25 (±5)℃. After the reaction is completed, all the liquid is transferred to a dialysis bag with a molecular weight of 8000-14000 and dialyzed for 4d. After the dialysis is completed, a nanocellulose suspension is obtained, and nanocellulose is obtained by freeze drying.
[0054] (4) Preparation and modification of aerogel: Take 0.3g of polyvinyl alcohol and thoroughly dissolve it in 99.2g of deionized water, then add 0.5g of nanocellulose. Place the mixture in an ultrasonic container for 30 minutes to fully cross-link the nanocellulose and polyvinyl alcohol. Then freeze-dry the mixture to obtain nanocellulose aerogel. Place the aerogel together with 1mL of deionized water and 3mL of MTMS in a sealed container and perform chemical vapor deposition reaction in a vacuum drying oven at 70°C. After 6 hours, nanocellulose modified aerogel is obtained.
[0055] (5) To verify the hydrophobic effect of aerogels, the aerogels were immersed in an oil-water mixture (the oil stains can be dyed with Sudan red dye). It can be observed that the nanocellulose-modified aerogels float on the water surface and quickly absorb the oil stains while still floating on the water surface.
[0056] The nanocellulose obtained in this experiment showed an intertwined mesh structure under a transmission scanning electron microscope. The density of the U-nanocellulose modified aerogel is 8.25 kg / m 3 The porosity is 99.36%, the water contact angle is 118.6°, and the amount of oil adsorbed is about 38g / g. Example 5
[0057] A method for preparing hydrophobic nanocellulose aerogel using bagasse as raw material, comprising the following steps: (1) Pretreatment: Soak the bagasse in warm water at 70°C overnight, then filter and wash with clean water until the filtrate is clear; then place it in a 60°C air drying oven to dry it so that the moisture content is kept at 10%; finally grind it with a crusher, sieve it, and collect the bagasse powder on the 60-mesh sieve. Take 5g of bagasse powder, mix it with 20mL of anhydrous ethanol and 40mL of toluene, and stir and heat it at 110°C for 6h. After the reaction is completed, wash the filter residue with anhydrous ethanol and ultrapure water in turn, and then place it in a 60°C air drying oven to dry it.
[0058] (2) Cellulose extraction: Take 3 g of the sample obtained in step (1), mix it with 105 g of 10% KOH solution, and stir and heat it at 90°C for 4 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Then take 2 g of the dried filter residue and mix it with 66 g of 7.5% NaClO2 solution, adjust the pH to 3-4 with acetic acid, and stir and heat it at 75°C for 2 h. After the reaction is completed, wash the filter residue repeatedly with deionized water until the filtrate is neutral. Collect the filter residue and dry it in a 60°C forced air drying oven to obtain cellulose.
[0059] (3) Preparation of nanocellulose: Take 1g of cellulose obtained in step (2), disperse it in 100mL of deionized water, and stir it on a magnetic stirrer for 1h. Then add 0.16g of NaBr and 0.016g of TEMPO, move it into an ultrasonic cleaner and continue stirring. After adding 20mmol of NaClO, the oxidation reaction begins. As the reaction proceeds, the pH of the system will change. NaOH and HCl need to be used to maintain the reaction pH at 10.2. When the reaction pH remains constant, pour 15mL of anhydrous ethanol to quench the oxidation reaction and the reaction ends. The frequency of the ultrasonic cleaner is 40khz. Long-term ultrasound will increase the temperature. The temperature of the circulating liquid needs to be controlled at 25 (±5)℃. After the reaction is completed, all the liquid is transferred to a dialysis bag with a molecular weight of 8000-14000 and dialyzed for 4d. After the dialysis is completed, a nanocellulose suspension is obtained, and nanocellulose is obtained by freeze drying.
[0060] (4) Preparation and modification of aerogel: Take 0.3g of polyvinyl alcohol and thoroughly dissolve it in 99.2g of deionized water, then add 0.5g of nanocellulose. Place the mixture in an ultrasonic container for 30 minutes to fully cross-link the nanocellulose and polyvinyl alcohol. Then freeze-dry the mixture to obtain nanocellulose aerogel. Place the aerogel together with 1mL of deionized water and 3mL of MTMS in a sealed container and perform chemical vapor deposition reaction in a vacuum drying oven at 70°C. After 6 hours, nanocellulose modified aerogels were obtained.
[0061] (5) To verify the hydrophobic effect of aerogels, the aerogels were immersed in a mixture of oil and water (the oil stains can be dyed with Sudan red dye). It can be observed that the nanocellulose-modified aerogels float on the water surface and quickly absorb the oil stains while still floating on the water surface. The nanocellulose obtained in this experiment showed an intertwined network structure under a transmission scanning electron microscope. The density of the nanocellulose modified aerogel is 11.67 kg / m 3 The porosity is 99.10%, the water contact angle is 112.7°, and the amount of oil adsorbed is 36g / g.
[0062] The effects of Example 4 and Example 5 are not as good as the results in Example 1. This is because, in the process of extracting cellulose using wine lees as raw materials, the experimental parameters were optimized. In this case, the cellulose extracted from wheat straw and sugarcane bagasse has a low purity, which affects the subsequent preparation and modification of nanocellulose. However, after modification, the nanocellulose aerogel still has excellent hydrophobicity, high porosity, low density, and high oil adsorption capacity. It shows that the preparation and modification method of the nanocellulose aerogel of the present invention is suitable for different biomass raw materials.
[0063] The modified aerogel obtained by the present invention has excellent hydrophobicity, can be used to adsorb oil in an oil-water mixture, and has great development potential in dealing with problems such as oil-water separation and offshore oil spills. The obtained aerogel is immersed in an oil-water mixture, and the oil can be quickly adsorbed by the aerogel. After the adsorbed oil is removed by an organic solvent, after 10 oil removals, the aerogel still has stable oil adsorption and good recyclability. In addition, due to its high porosity and high specific surface area, it can be used as an adsorbent in the field of water purification, such as adsorption of heavy metals and adsorption of dyes. Due to its good biocompatibility, it can also be used in the biomedical field, such as drug carriers, tissue engineering and wound dressings.
[0064] The above is an embodiment of the present invention with better experimental effects, and does not impose any form of limitation on the present invention. Any technical solution that does not deviate from the present invention and any parameter modification made to the embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing hydrophobic nanocellulose aerogel using wine lees as raw material, characterized in that: The following steps are involved: The wine lees residue is washed and dried, ground and mixed with a pretreatment liquid to remove impurities to obtain wine lees powder; the wine lees powder is reacted with an alkali solution and a bleaching solution to obtain cellulose; the cellulose is subjected to TEMPO oxidation and ultrasound, dialyzed and freeze-dried to obtain nanocellulose; the nanocellulose is mixed with a polyvinyl alcohol solution, freeze-dried to obtain a nanocellulose aerogel, and then silanized by chemical vapor deposition to obtain a hydrophobic nanocellulose aerogel.
2. The method for preparing hydrophobic nanocellulose aerogel using wine lees as raw material according to claim 1, characterized in that: Before washing the lees, they are completely soaked in water at about 70-90°C, then washed with deionized water until the filtrate is clear, and then dried in an oven at 60-80°C.
3. The method for preparing hydrophobic nanocellulose aerogel using wine lees as raw material according to claim 1, characterized in that: The pretreatment liquid is a mixture of toluene and ethanol, the volume ratio of toluene to ethanol is 1-3:1, and the ratio of vinasse to pretreatment liquid is 1:12-15.
4. The method for preparing hydrophobic nanocellulose aerogel using wine lees as raw material according to claim 1, characterized in that: The wine lees are immersed in the pretreatment liquid with dynamic heating and stirring at a temperature of 90~110℃ for 6-8h; after being treated with the pretreatment liquid, they are washed with ethanol and deionized water in turn, and then placed in a 60℃-80℃ oven for drying and storage.
5. The method for preparing hydrophobic nanocellulose aerogel using wine lees as raw material according to claim 1, characterized in that: The alkali solution is a 5%-15% KOH solution; the reaction temperature of the vinasse powder and the alkali solution is 70-90°C, the reaction time is 2-4h, and the solid-liquid ratio is 1:15-35; the bleaching solution is a 1.5%-7.5% NaClO2 solution; the reaction temperature of the vinasse powder and the bleaching solution is 75-95°C, the reaction time is 1.5-2.5h, and the solid-liquid ratio is 1:30-35; acetic acid is used to adjust the pH during the reaction of the vinasse powder and the bleaching solution so that the pH is maintained at 3-4; the filter residue after the alkali solution treatment and the bleaching solution treatment is repeatedly washed with deionized water until the filtrate is neutral, and then placed in a 60-80°C oven for drying.
6. The method for preparing hydrophobic nanocellulose aerogel using wine lees as raw material according to claim 1, characterized in that: The TEMPO oxidation adopts a TEMPO / NaBr / NaClO catalytic oxidation system, the mass ratio of TEMPO to NaBr is 1:5-16, the mass ratio of cellulose to NaBr is 1:0.16-0.33, and the amount of NaClO is 5-30mmol / g cellulose; before the TEMPO oxidation reaction, the cellulose is dispersed in ultrapure water with a solid-liquid ratio of 1:80-120, and stirred at room temperature for 1-2h; the TEMPO oxidation reaction is carried out in an ultrasonic cleaner throughout the process, the ultrasonic power is 30-50kHz, and the temperature is controlled at 25 (±5)°C by a cooling circulating fluid.
7. The method for preparing hydrophobic nanocellulose aerogel using wine lees as raw material according to claim 1, characterized in that: During the TEMPO oxidation reaction, HCl and NaOH are used to maintain the pH of the reaction in the range of 10-11; when the pH remains constant, 5-30 ml mL of anhydrous ethanol is poured in to quench the oxidation reaction; dialysis uses a dialysis bag with a molecular weight of 8000-14000, and the dialysis time is 3-5 days. After dialysis, a nanocellulose suspension is obtained, and nanocellulose is obtained after freeze-drying.
8. The method for preparing hydrophobic nanocellulose aerogel using wine lees as raw material according to claim 1, characterized in that: The modifier used for silanization modification is methyltrimethoxysilane, the modification temperature is 70~80℃, and the time is 5~7h.
9. A hydrophobic nanocellulose aerogel, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. Use of the hydrophobic nanocellulose aerogel according to claim 9 in oil pollution adsorption.
